A Coached Digital Cognitive Behavioral Intervention Reduces Anxiety and Depression in Adults With Functional Gastrointestinal Disorders. Issue 12 (7th December 2021) - Szigethy, Eva; Tansel, Aylin; Pavlick, Alexa N.; Marroquin, Maria A.; Serio, Catherine D.; Silfee, Valerie; Wallace, Meredith L.; Kingsley, Michael J.; Levinthal, David J.
Abstract : INTRODUCTION: Traditional cognitive behavioral interventions (CBIs) improve mood and gastrointestinal symptom severity in patients with functional gastrointestinal disorders (FGIDs) but face substantial barriers to implementation. Integrating behavioral health technology into medical clinic workflows could overcome these barriers. We evaluated the feasibility and impact of a coached digital CBI (dCBI) as a first-line intervention in a prospective cohort of emotionally distressed patients with FGID. METHODS: Patients with anxiety and/or depressive symptoms were offered a dCBI (an app called RxWell) during routine clinic visits. RxWell provides cognitive behavioral techniques enhanced by within-app text messaging with a health coach. Both gastroenterology and behavioral health-care providers electronically prescribed RxWell. We tracked patient interactions with RxWell, and patients completed anxiety (General Anxiety Disorder-7) and depression (Personal Health Questionniare Depression Scale) measures through the app. Our primary study outcome was the change in General Anxiety Disorder-7 and Personal Health Questionniare Depression Scale scores. RESULTS: Of 364 patients with FGID (mean age 43 years [SD 16 years]; 73.1% women) prescribed the dCBI, 48.4% enrolled (median use, 3 techniques [interquartile range 1–14]). About half of RxWell enrollees communicated with health coaches. The mean baseline anxiety score was 11.4 (SD 5.5), and the depression score was 11.5 (SD 6.1). RxWell users experienced improvements in anxiety (mean change 2.71 [ t = 3.7, df = 58; P < 0.001]) and depression (mean change 2.9 [ t = 4.2, df = 45; P < 0.001]) at 4 months. DISCUSSION: Patients with FGIDs and moderately severe anxiety and depressive symptoms are willing to use dCBI tools recommended by their providers. Our pilot data demonstrate that dCBI usage is associated with clinically and statistically significant mood symptom reductions.